Image Processing: A Smart Technology for Early Detection of Crop Pests and Diseases - Pakeerathan, K. (Department of Agricultural Biology, University of Jaffna, Jaffna, Sri Lanka, 2023)
There is an urgent need for the developing countries and Island States to produce sufficient quantities food to eliminate hunger and malnutrition of the ever-increasing human population. Smallholder farms are a crucial part of food systems and play a major role in food production. Farmers in Island nations are facing serious difficulties due to climate change and to increase their agricultural production. In this context, Smart farming is the only weapon in the farmer’s hand to win against climate change. Smart farming is a new concept that bridges traditional practices with modern agricultural innovations, tools, and policies to produce food in the face of changing and varying climatic conditions. However, the majority of the farmers in small Island nations are facing severe challenges to adopt and implement Smart agricultural technologies and transform their traditional farms into Smart farms. This chapter extensively addresses the issues and challenges faced by the farmers in Smart agriculture and provide strategic solutions to young researchers and scientists working in this field by supporting examples from the small Island nations. Further, this chapter suggests a few recommendations for policies and strategies that should be adopted by the governments of the Island nations, policymakers, and other stakeholders on how they all should work together to promote Smart agriculture.
Keywords: Agricultural Policy; Challenges; Island states; Scientific knowledge; Strategies